2017
DOI: 10.1002/da.22655
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty increases neural indices of attention in obsessive-compulsive disorder

Abstract: These results suggest that OCD patients process anticipation of inevitable and potential threat similarly and highlight the substantial motivational impact of uncertain events to OCD patients. Finally, the correlation with anxiety implies that anxiety represents the source of hypervigilance during uncertainty resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 44 publications
3
18
1
Order By: Relevance
“…Sussman et al's (2017) functional magnetic resonance imaging (fMRI) study showed that cues indicating upcoming threat increased amygdala activity (a brain region associated with emotional attention) for subsequently presented threat faces. Moreover, studies on uncertainty have shown that attention towards the event, particularly the emotional event, is altered by cue uncertainty due to worry and anxiety, motivation and biased expectancies of negative consequences (e.g., Nitschke, 2011, 2013;Dieterich et al, 2016Dieterich et al, , 2017; for a review, Anselme, 2010). In line with those studies, Sarinopoulos et al (2010) showed stronger amygdala responses to uncertainty compared to certain negative events.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…Sussman et al's (2017) functional magnetic resonance imaging (fMRI) study showed that cues indicating upcoming threat increased amygdala activity (a brain region associated with emotional attention) for subsequently presented threat faces. Moreover, studies on uncertainty have shown that attention towards the event, particularly the emotional event, is altered by cue uncertainty due to worry and anxiety, motivation and biased expectancies of negative consequences (e.g., Nitschke, 2011, 2013;Dieterich et al, 2016Dieterich et al, , 2017; for a review, Anselme, 2010). In line with those studies, Sarinopoulos et al (2010) showed stronger amygdala responses to uncertainty compared to certain negative events.…”
Section: Introductionmentioning
confidence: 77%
“…Some of these emotional and non-emotional cues signify upcoming events with certainty (i.e., they are certain cues), whereas others do not (i.e., they are uncertain cues). The different categories of cues might critically influence the perception of emotional consequences and even guide decision-making associated with those consequences (e.g., Onoda et al, 2006Onoda et al, , 2007Onoda et al, , 2008Sarinopoulos et al, 2010;Grupe and Nitschke, 2011;Gole et al, 2012;Lin et al, 2012Lin et al, , 2014aLin et al, ,b, 2015aLin et al, ,d, 2017bLin et al, , 2018Yang et al, 2012;Aue et al, 2013;Dieterich et al, 2016Dieterich et al, , 2017Sussman et al, 2017;Qiao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the human literature, substantial research has supported the notion that individual differences in the sensitivity to cues may also confer risk for anxiety disorders (Bar-Haim, Lamy, Pergamin, Bakermans-Kranenburg, & van IJzendoorn, 2007;Heeren, Peschard, & Philippot, 2011;Mogg & Bradley, 2018;Shackman et al, 2016;Van Bockstaele et al, 2014). However, the majority of this work has examined abnormalities in neural, cognitive, and behavioral reactivity towards threat cues versus neutral cues, or compared to healthy control populations (e.g., Dieterich, Endrass, & Kathmann, 2017). Within this line of work, uncertainty has emerged as an important moderator of this observed individual difference in sensitivity to threat cues, with individuals with anxiety disorders demonstrating enhanced reactivity to uncertain compared to certain threat cues (Bradford, Kaye, & Curtin, 2014a;Bradford, Magruder, Korhumel, & Curtin, 2014b;Grupe & Nitschke, 2013).…”
Section: Cue Sensitivity and Sensitization By Stressmentioning
confidence: 99%